Observation of a photoinduced, resonant tunneling effect in a carbon nanotube–silicon heterojunction - Aramo, Carla; Ambrosio, Antonio; Ambrosio, Michelangelo; Boscardin, Maurizio; Castrucci, Paola; Crivellari, Michele; Cilmo, Marco; De Crescenzi, Maurizio; De Nicola, Francesco; Fiandrini, Emanuele; Grossi, Valentina; Maddalena, Pasqualino; et al. (Beilstein Journal of Nanotechnology, 2015)
A significant resonant tunneling effect has been observed under the 2.4 V junction threshold in a large area, carbon nanotube–silicon (CNT–Si) heterojunction obtained by growing a continuous layer of multiwall carbon nanotubes on an n-doped silicon substrate. The multiwall carbon nanostructures were grown by a chemical vapor deposition (CVD) technique on a 60 nm thick, silicon nitride layer, deposited on an n-type Si substrate. The heterojunction characteristics were intensively studied on different substrates, resulting in high photoresponsivity with a large reverse photocurrent plateau. In this paper, we report on the photoresponsivity characteristics of the device, the heterojunction threshold and the tunnel-like effect observed as a function of applied voltage and excitation wavelength. The experiments are performed in the near-ultraviolet to near-infrared wavelength range. The high conversion efficiency of light radiation into photoelectrons observed with the presented layout allows the device to be used as a large area photodetector with very low, intrinsic dark current and noise.
Keywords: heterojunction; multiwall carbon nanotubes; NDR; photodetector; tunneling

Physics of Semiconductor devices - Sze, S. M. (John Wiley & Sons, 1969)

The physics of low dimensional semiconductors. An introduction - Davies, J. (Cambridge University Press, 1998)

(untitled) - Liu, Q.; Yu, L.; Li, H.; Qin, R.; Jing, Z.; Zheng, J.; Gao, Z.; Lu, J. (J. Phys. Chem. C, 2011)

(untitled) - Liu, Q.; Luo, G.; Qin, R.; Li, H.; Yan, X.; Xu, C.; Lai, L.; Zhou, J.; Hou, S.; Wang, E. (Phys. Rev. B, 2011)

(untitled) - Rinkiö, M.; Johansson, A.; Kotimäki, V.; Törmä, P. (ACS Nano, 2010)

(untitled) - Nguyen, P. D.; Nguyen, T. C.; Hossain, F. M.; Huynh, D. H.; Evans, R.; Skafidas, E. (Nanoscale, 2015)

(untitled) - Britnell, L.; Gorbachev, R. V.; Geim, A. K.; Ponomarenko, L. A.; Mishchenko, A.; Greenaway, M. T.; Fromhold, T. M.; Novoselov, K. S.; Eaves, L. (Nat. Commun., 2013)

(untitled) - Konstantatos, G.; Sargent, E. H. (Nat. Nanotechnol., 2010)

(untitled) - Kenny, J. T.; Pollock, H. R. (Infrared Phys. Technol., 2001)

(untitled) - Itkis, M. E.; Borondics, F.; Yu, A.; Haddon, R. C. (Science, 2006)

(untitled) - Lu, S.; Panchapakesan, B. (Nanotechnology, 2006)

(untitled) - Levitsky, I. A.; Euler, W. B. (Appl. Phys. Lett., 2003)

(untitled) - Ambrosio, A.; Aramo, C.; Battiston, R.; Castrucci, P.; Cilmo, M.; De Crescenzi, M.; Fiandrini, E.; Grossi, V.; Guarino, F.; Maddalena, P.; Nappi, E.; Passacantando, M.; et al. (J. Instrum., 2012)

(untitled) - Passacantando, M.; Bussolotti, F.; Grossi, V.; Santucci, S.; Ambrosio, A.; Ambrosio, M.; Ambrosone, G.; Carillo, V.; Maddalena, P.; Perillo, E.; Raulo, A. (Appl. Phys. Lett., 2008)

(untitled) - Tinti, A.; Righetti, F.; Ligonzo, T.; Valentini, A.; Nappi, E.; Ambrosio, A.; Ambrosio, M.; Aramo, C.; Maddalena, P.; Castrucci, P.; Scarselli, M.; De Crescenzi, M.; et al. (Nucl. Instrum. Methods Phys. Res., Sect. A, 2011)

(untitled) - Aramo, C.; Ambrosio, A.; Ambrosio, M.; Battiston, R.; Castrucci, P.; Cilmo, M.; De Crescenzi, M.; Fiandrini, E.; Grossi, V.; Guarino, F.; Maddalena, P.; Nappi, E.; et al. (Nucl. Instrum. Methods Phys. Res., Sect. A, 2013)

(untitled) - Aramo, C.; Ambrosio, A.; Ambrosio, M.; Battiston, R.; Castrucci, P.; Cilmo, M.; De Crescenzi, M.; Fiandrini, E.; Grossi, V.; Guarino, F.; Maddalena, P.; Nappi, E.; et al. (EPJ Web Conf., 2013)

(untitled) - Castrucci, P.; Scilletta, C.; Del Gobbo, S.; Scarselli, M.; Camilli, L.; Simeoni, M.; Delley, B.; Continenza, A.; De Crescenzi, M. (Nanotechnology, 2011)